Consciousness in the Universe - Chamcham, Khalil (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
So far we can identify at least three concepts within modern cosmology that bring into debate the question of consciousness in the universe: 1) Fine Tuning; 2) The Anthropic Principle and 3) The Multiverse. This does not exclude the question of the role of observer (i.e. consciousness) in cosmology as developed within Quantum Physics: we observe the universe through quanta and any breakthrough in understanding the origin and nature of the universe will come only through a quantum theory of gravity […]